Impact of E-cigarettes and vaping on periodontal health: A narrative review - Sayeed Rahman, Ghousia (Asian Journal of Pharmaceutics (AJP), 2025)
The use of electronic cigarettes, “e-cigarettes,” or vaping is growing in popularity, especially among adolescents and young adults. While the effects of cigarette smoking on oral health are well-established, the exact impact that e-cigarettes may have on dental tissues is still uncertain. The current review aimed to summarize evidence related to the effect of vaping on the periodontal health status of e-cigarette users. A comprehensive electronic search was conducted on the PubMed, Scopus, and Embase databases using the following search terms: Electronic cigarettes OR vaping OR electronic nicotine delivery systems OR e-cigarettes AND periodontitis. The search was limited to studies published from 2022 to 2025. The full-text articles published in the English language were selected for the review purpose. Thirty-nine clinical studies focusing on the effect of e-cigarette smoking on the periodontal clinical parameters, levels of inflammatory mediators, alteration in periodontal micro flora, and response to periodontal treatment were found to be eligible for inclusion in the review. Vaping may be associated with greater clinical attachment loss compared to non-smokers. Moreover, ECs are also associated with unfavorable effects on periodontal microbial counts, biomarkers of inflammation, and oxidative stress. Electronic cigarettes, “e-cigarettes,” or vaping may play a role in the initiation and progression of periodontal disease by altering the host response, resulting in the release of inflammatory cytokines and periodontal microflora. Clinical studies show deleterious effects of vaping on periodontal health, as well as less favorable response to periodontal treatment is observed in e-cigarette users compared to non-smokers.